Laser welding of precipitation strengthened Ni-rich NiTiHf high temperature shape memory alloys: Microstructure and mechanical properties. (15th January 2019) - Oliveira, J.P.; Schell, N.; Zhou, N.; Wood, L.; Benafan, O.
Abstract: High temperature shape memory alloys are currently attracting significant attention by the aerospace industry due to the potential use of shape memory and superelastic properties at temperatures above 100 °C. Virtually any advanced engineering material must, at some point, be joined either to itself, to create complex shaped structures, or to other materials to increase its potential applications. In this work, laser welding of a precipitation strengthened Ni-rich NiTiHf high temperature shape memory alloy is reported for the first time. Starting with a base material aged at 500 °C for 3 h and air cooled, defect-free joints with a conduction weld mode were obtained. Microstructural characterization, facilitated via microscopy and synchrotron X-ray diffraction, revealed that the fusion zone contained a single-phase martensitic structure at room temperature, compared to a mixture of martensite and H-phase precipitates in the base material. Isothermal loading in both the martensite (at 30 °C) and austenite (at 200 °C) phases revealed equivalent strength and near-perfect superelasticity in the welded and un-welded reference material. Graphical abstract: Highlights: First report on welding of NiTiHf high temperature shape memory alloys Synchrotron X-ray diffraction was used for microstructural mapping. The welded joint exhibited shape memory effect and superelasticity comparable to the base material.